2007
DOI: 10.1002/ibd.20058
|View full text |Cite
|
Sign up to set email alerts
|

Role of capsule endoscopy in inflammatory bowel disease

Abstract: Videocapsule endoscopy (VCE) has revolutionized our ability to visualize the small bowel mucosa. This modality is a valuable tool for the diagnosis of obscure small bowel Crohn's disease (CD), and can also be used for monitoring of disease activity in patients with established small-bowel CD, detection of complications such as obscure bleeding and neoplasms, evaluation of response to anti-inflammatory treatment and postoperative recurrence following small bowel resection. VCE could also be an important tool in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
33
0
2

Year Published

2008
2008
2014
2014

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(35 citation statements)
references
References 92 publications
0
33
0
2
Order By: Relevance
“…Lastly, capsule endoscopy has emerged as a relatively noninvasive method for direct evaluation of the small bowel mucosa (49)(50)(51)). Yet, individual study sizes have been small, and the yield of CE for the initial diagnosis of CD versus evaluation of recurrent, known disease remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, capsule endoscopy has emerged as a relatively noninvasive method for direct evaluation of the small bowel mucosa (49)(50)(51)). Yet, individual study sizes have been small, and the yield of CE for the initial diagnosis of CD versus evaluation of recurrent, known disease remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…8 In the setting of IBDU/IC, several studies on the benefit of CE for its evaluation have been published. [6][7][8] These small pilot studies found that the use of CE led to a change in the diagnosis of 29%-40% of patients. 6 A recent multicenter study 7 looked at 30 seronegative IBDU/IC patients with a mean duration of disease of 6 years (range 1-18).…”
Section: Discussionmentioning
confidence: 99%
“…[6][7][8] These small pilot studies found that the use of CE led to a change in the diagnosis of 29%-40% of patients. 6 A recent multicenter study 7 looked at 30 seronegative IBDU/IC patients with a mean duration of disease of 6 years (range 1-18). An initial CE was positive in 5 patients, with a mean duration of disease of 4 years (range 1-9), who were later diagnosed with CD.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations